Peripheral and intestinal mucosal-associated invariant T cells in premature infants with necrotizing enterocolitis - Tian, Jiayi; Yan, Chaoying; Jiang, Yanfang; Zhou, Haohan; Li, Liyuan; Shen, Jingjing; Wang, Jian; Sun, Hongyu; Yang, Guang; Sun, Wei (Frontiers in Pharmacology, 2022)
Background: Necrotizing enterocolitis (NEC) is a potentially fatal inflammatory gastrointestinal disease in preterm infants with unknown pathogenesis. Mucosal-associated invariant T (MAIT) cells primarily accumulate at sites where exposure to microbes is ubiquitous and regulate immunological responses. As the implications of these cells in NEC development in premature infants remain unknown, we investigated the role and characteristics of MAIT cells in NEC pathogenesis. Methods: The percentage of different MAIT cell subsets in peripheral blood samples of 30 preterm infants with NEC and 22 control subjects was estimated using flow cytometry. The frequency of MAIT cells in the intestinal tissues of 5 NEC patients and 5 control subjects was also examined. The level of serum cytokines was estimated using cytometric bead array. Potential associations between the different measurements were analyzed using the Spearman’s correlation test. Results: Compared with controls, the NEC patients were found to have significantly reduced percentages of circulating CD161+CD3+CD8αα+ T cells and CD161+CD3+ TCRγδ-TCRVa7.2+ MAIT cells. In the intestinal tissues, the percentage of MAIT cells was significantly higher in samples from the NEC patients than the controls. Furthermore, the percentage of circulating MAIT cells in the peripheral blood samples was inversely correlated with that in the intestinal tissues of the NEC patients. The percentage of CD8αα+ MAIT cells was found to be significantly reduced in both peripheral blood and intestinal tissues of NEC patients. Following treatment, the frequency of circulating MAIT cells significantly increased in NEC patients and reached a level similar to that in the control subjects. However, there was no difference in the percentage of circulating CD8αα+ MAIT cells before and after treatment in the NEC patients. Conclusion: Our results suggested that during the development of NEC MAIT cells accumulate in the inflammatory intestinal tissues, while CD8αα upregulation in response to gut environment is not initiated properly, which may lead to the dysfunction of MAIT cells in gut immunity. An immune tolerance related mechanism may be involved in preterm infants NEC pathogenesis, and more functional studies are needs to verify this hypothesis.